Private sector involvement in the euro : the power of ideas - Collignon, Stefan, 1951- (Routledge, 2003)
This book looks at the role of the Association for Monetary Union in Europe's role in the construction of the Euro.
Keywords: Economic and Monetary Union.; Economic and Monetary Union; Euro.; Monetary unions -- European Union countries.; Monetary policy -- European Union countries.; Non-governmental organizations.; Euro (Monnaie); Unions monétaires -- Pays de l'Union européenne.; Politique monétaire -- Pays de l'Union européenne.; Organisations non gouvernementales.; BUSINESS & ECONOMICS -- Money & Monetary Policy.; Euro; Monetary policy; Monetary unions; Non-governmental organizations; European Union countries